Tracking the storage root bulking of cassava under split application of fertilizer nutrients - Omondi, J.O.; doRosario, N.; Manda, N.; Ntawuruhunga, P.; Parkes, E.; Mushoriwa, H.; Mbuthia, L.W.; Kyei-Boahen, S. (Frontiers Media, 2025)
Cassava is important as food, feed, and raw material, yet its root architecture is not fully understood and thoroughly studied, thereby limiting the realization of its full potential. Compounding this is the common practice of applying fertilizer to cassava at planting without extensive knowledge of the suitable growth stage or time for optimal nutrient uptake. Consequently, this study’s objective was to stagger fertilizer application in split doses to synchronize nutrient uptake and cassava growth and track the storage root bulking process. Nine treatments of normal and controlled-release fertilizers were tested in the field, each applied in four splits at 0, 2, 4, and 6 months after planting (MAPs) to the Binte Massude cassava variety. The results indicated that controlled-release fertilizers applied in two splits at planting and 6 MAPs led to 19.0% greater root yield, whereas normal fertilizers applied in four splits every 2 months led to 22.7% greater root yield compared to not applying fertilizer to cassava. Irrespective of the fertilizer form, when the number of roots increased, the root yield decreased gradually, while root diameter and root length had a direct relationship with storage root yield. Furthermore, the relationship between root number and either root diameter or root length was significantly inverse. This study has successfully indicated the root attributes that can be observed to predict storage root yield, and that staggering fertilizer application in targeted splits increases root yield, however, this must be synchronized with moisture availability for optimal benefit.